(untitled) (Journal of Philosophy Culture and Political Science, 2024)
This work is devoted to the study of the influence of Turkic ideology and political values on Kazakhstan. In modern Kazakh society, organizational forms can be traced aimed at developing and improving perception as a Turkic people. The purpose of the work is to determine the factors influencing the formation of political values and Turkic ideology in Kazakhstan, as well as to determine the degree of influence of these factors. The relevance of the work is due to the increased interest in the politics of Central Asia and the growing political influence of Kazakhstan. The research methodology was a survey of residents using analysis of the data obtained. The basis for the study was the works of domestic researchers such as: Zhetpysbaev S., Ayimbet Zh., Zhenis Zh., Sapiev E., Turkish researchers: Oktem K., Seytak B., Chemil D. and foreign scientists: Avatkov A., Khlikhor E. and others. The work examines the reasoning of researchers on the issue of the formation of Turkic ideology and identity. The ideas of a nomadic way of life, a common history, as well as linguistic similarities are presented as the basis for the formation of Turkic identity. This work will present a different approach to the formation of Turkic identity and ideology, namely the study of everyday aspects of society. As the basis of political values, many researchers highlight such aspects as: political organizations, cultural proximity, social interaction. Key words: Kazakhstan, political values, ideology of the Turks, Turks, politics, values, economics, society.